Key success factors of TQM organizations : a review of the literature / Mohammad Zaki Ayob and Fatimah Mohd Saman - Ayob, Mohammad Zaki; Mohd Saman, Fatimah (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
The use of Total Quality Management (TQM) philosophy has increased over the years. TQM organizations have been found to out-perform the non-TQM organizations on several measures of organizational performance and employee satisfaction. Although some TQM programs may fail due to various reasons, the benefits such as better understanding of customers and improved employee performance are reasons for continued interest in TQM. This article attempts to review the literature on TQM. It seeks to provide the different perspectives on quality, defines TQM, traces its origin, and highlights the quality 'gurus'. At the end, the key elements contributing to the successful implementation of TQM are discussed.